The transformation of ontology dimension of image in aesthetics - Daraškevičiūtė, Vaiva (Religija ir kultūra, 2009)
This article predicates on two thesis. The first one proposes that the ontological dimension of the image should not be discussed in any other way but in the light of Martin Heidegger’s hermeneutical philosophy’s perspective, i.e., after the conceptions of being, truth, and artwork have already varied. This thesis is supported by three arguments: the image could be the place where the truth – as it is in it’s ontological meaning – reveals itself (Heidegger); interpretation is the only method we are capable to use in recognizing an artwork (Pareyson); the image enables the new reality (Gadamer). The second thesis states that the ontological dimension of an image does not dissapear in the postmodern era though it seems that neither the ontology of the reality nor that of an artwork are longer visible. The thesis is based on Gianni Vattimo’s weak thinking philosophy.